Evaluation of bioagents against Sclerotinia sclerotiorum causing Sclerotinia rot of Indian mustard - Jitendra Sharma; Shailesh Godika; RP Ghasolia; Shashi Kant Goyal; Arjun Lal Yadav (Journal of Oilseed Brassica, 2026)
Among the fungal diseases, Sclerotinia rot caused by Sclerotinia sclerotiorum (Lib.) de Bary, is the mostdestructive disease of Indian mustard [Brassica juncea (L.) Czern & Coss.], and its management withchemicals is not economically viable, and environmentally safe. Therefore, the present investigations wereaimed to carry out the test of bioagents against S. Sclerotiorum under in-vitro and in-vivo conditions. Invitro,screening of bioagents (Bacillus subtilis, Trichoderma harzianum and T. viride) was done by dualculture technique. All the bio agents viz., Bacillus subtilis, T. harzianum, and T. viride were antagonistic tothe growth of S. sclerotiorum. Maximum 69.8 % mycelial growth inhibition of pathogen was recorded with T.viride, and minimum mycelial growth inhibition was recorded by Bacillus subtilis (42.2%). Results underfield conditions revealed that minimum disease intensity (26.0 %) was recorded with seed + soil application ofT. viride followed by soil application of T. viride (35.7 %) as compared to control (68.3 %).